Eletromolhamento em filmes dielétricos super-hidrofóbicos - Rocha, Hérica Dias da (2016)
Monolayer and bilayer superhydrophobic films obtained from the spray 1 and 2 of commercial product NeverWet were successfully prepared. For these systems, we have studied the influence of the drying conditions (atmospheric pressure and vacuum) on their surface morphologies as well as the electrowetting on dielectric (EWOD) effect. For the monolayer films from spray 1, the study of the surface morphologies exhibits dark protuberances smaller than those found in films obtained under vacuum. The monolayer films from spray 2 under vacuum condition show morphologies more uniforms when compared with those observed for the monolayer films of spray 1. The influence of the drying conditions on EWOD of the monolayer of films from spray 2 was also examined. The monolayer films dried under vacuum condition exhibit a better electrowetting response that those obtained from spray 1. For monolayer films of spray 2, we also investigated the influence of the UV irradiation (254 nm) on the EWOD. Under drying at atmospheric pressure, it is observed that the EWOD contact angle behavior is independent of the irradiation time. On the other hand, the films dried under vacuum exhibit different behaviors depending on the irradiation time. These results suggest that is possible using the UV irradiation in controlling of the EWOD. For bilayer films, it is found that their surface morphologies are not uniform. These films have several cracks and dark lumps along their surfaces and, although they are superhydrophobic and have EWOD. Moreover, the drying condition does not affect significantly the EWOD. Finally, the monolayer films of spray 2 have potential for applications in EWOD-based devices.